Development of 0d and 2d materials for water remediation, hydrogen evolution reaction, and cancer treatment - Freire, Tiago Melo (2021)
Magnetite/chitosan nanocomposites were able to remove dyes from textile effluents. Thus, a comparative study of these materials toward adsorption of reactive black 5 and methyl orange showed a pH-dependent adsorption capacity, with pH 4 being more indicated for crosslinked samples and pH 8 for non-modified material. Indeed, it demonstrated that the adsorption capacity is influenced by molecular size effect and electrostatic attraction for unmodified and modified nanocomposites, respectively. In the second moment, bimetallic FeM (M = Ag, Co, Cu, and Ni) materials were synthesized by thermal decomposition for hydrogen production application. These samples presented soft ferrimagnetic behaviour and varied morphology depending of the composition (e.g., spheres, cubes, and triangles). However, the samples containing Ag and Cu showed a bimodal size distribution, possibly due to the significant difference between the reduction potential of these metals and ferric ions, which generates different nucleation rates. Electrocatalytic tests showed that the FeCu alloy performed better due to its lower overpotential (494 mV) compared to the other alloys, and all electrocatalysts were stable during the 8 h period of continuous operation. Finally, g-C3N4 was produced from the thermal polymerization of urea at 550° C for use in cancer treatment. The formation of a typical structure in the form of stacked C3N4 sheets was evidenced by XRD, FTIR, Raman, AFM, and TEM techniques. Analysis of XRD and XPS showed defects in the structure of g-C3N4 due to incomplete polymerization of urea, resulting in decreased interplanar space. The synthesized materials presented a band gap of 2.87 eV and an emission band at 448 nm, regardless of the exciting wavelength. Biological tests have shown excellent biocompatibility of g-C3N4 with normal cells and the inhibitory effect on cancer cell lines. Biodistribution tests in tissues indicated that the material accumulated in the lungs in the first two hours and was later found mainly in the liver after 24 hours. In this sense, g-C3N4 showed great potential for the treatment of various types of cancer.